Exploring the associations between resilience and psychological well-being among South Africans during COVID-19 - Sayed, Tasleem; Malan, Hanelie; Fourie, Erika (Frontiers in Psychology, 2024)
Resilience pertains to an individual's ability to withstand, adapt, and recuperate from adversity and stress. As the world grapples with unprecedented challenges such as the COVID-19 pandemic, understanding the relationship between resilience and psychological well-being becomes essential. Preliminary observations suggest that those with a higher resilience tend to have better psychological well-being, indicating a possible symbiotic relationship between the two. This study was structured using a cross-sectional survey design. A convenience sampling technique was employed, including 631 respondents in South Africa. Data collection took place between June 11 and July 9, 2022, facilitated through a Google Forms questionnaire. This questionnaire encompassed various instruments, namely a biographical questionnaire, the CD-RISC 10, the WHO Well-being Index, the FACIT-Sp-12, and the PMHS. The findings from the collected data highlighted a strong correlation between resilience and overall well-being during the COVID-19 pandemic. This elevation in resilience can be instrumental in augmenting psychological well-being. As such, interventions or programs aimed at enhancing individual and community well-being might benefit from incorporating elements that bolster resilience, especially during periods of global adversity.